Exposure to tobacco smoke measured by urinary nicotine metabolites increases risk of p16/Ki-67 co-expression and high-grade cervical neoplasia in HPV positive women: A two year prospective study. (October 2020) - White, Christine M.; Bakhiet, Salih; Bates, Mark; Ruttle, Carmel; Pilkington, Loretto J.; Keegan, Helen; O'Toole, Sharon A.; Sharp, Linda; O'Kelly, Ruth; Tewari, Prerna; Flannelly, Grainne; Martin, Cara M.; et al.
Highlights: While smoking is a risk factor for HPV and cervical lesions, little is known about its role in transforming HPV infections. Transforming HPV infections can be characterised by the presence of p16/Ki-67 dual expression. We used urinary nicotine metabolite concentrations to measure exposure to tobacco smoke. HPV positive women with elevated urinary nicotine metabolites were at a higher risk of testing p16/Ki-67 positive. p16/Ki-67 positive women with elevated urinary nicotine metabolites, were at a higher risk of CIN2+/CIN3+. Abstract: Background: Human papillomavirus (HPV) is considered the strongest epidemiologic risk factor for cervical cancer. However, it is not a sufficient cause given the high prevalence of transient infections. We examined the relationship between exposure to tobacco smoke, measured using urinary nicotine metabolite concentrations, and p16/Ki-67 co-expression in cervical smears and subsequent risk of developing CIN2+/CIN3+ lesions in HPV positive women. Methods: This prospective longitudinal study enrolled women presenting to colposcopy with cytological abnormalities LSIL/ASCUS at the National Maternity Hospital, Dublin. Women gave a urine sample which was used to perform the Nicotine Metabolite Assay (Siemens). HPV positive (HC2) cervical smears were stained by immunocytochemistry for p16/Ki-67 (CINtec PLUS, Roche). Two year follow-up data, including histological diagnosis, was collected for each woman. Crude and adjusted odds ratios were calculated using logistic regression to investigate associations between tobacco smoke, p16/Ki-67 positivity and CIN2+/CIN3 +. Results: In total, 275 HPV positive women were included. Women with nicotine metabolite concentrations above 500 ng/mL, indicative of smoking, were classified as smokers. Smokers were at an increased risk of testing positive for p16/Ki-67 (OR 1.678; 1.027−2.740) and CIN2+ and CIN3+ (OR 1.816; 1.107−2.977 and OR 2.453; 1.200−5.013) in compared to non-smokers. In p16/Ki-67 positive women, smoking further increased their risk of CIN2+/CIN3+ (OR 2.290; 1.017−5.159 and OR 3.506 (1.534−8.017). Conclusion: HPV positive women exposed to tobacco smoke are at a higher risk of testing positive for p16/Ki-67 co-expression. Risk of high-grade disease is almost doubled in women who are exposed to tobacco smoke.